Pemijatan pada Bayi Efektif Meningkatkan Berat Badan - Sinthia Rosanti Maelissa; Syulce Luselya Tubalawony (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2019)
ABSTRAKThe purpose of this research is to see the baby's weight development especially for 4 to 6 month when they are receiving message therapy in the working area of Saparua public health center,Saparua sub-district. To get a sample that represents the population is done by the purposive sampling method with 20 respondents. The primary data collection is done by observing the weight through weighing and filling out the questionnaire that is filled by baby's mother. Mean while secondary data is obtained from Saparua public health center. The data were analized by dividing groups into 2, 10 people are the treatment people and 10 people are the control people,than compared and tested Independent statistic T-test. The result of the research show that routine message therapy for baby with mesaage movements on the feed,stomach, chest,hands,back and streching movements can improve baby's weight. The message therapy can stimulates intestinal peristaltic development and improve the gastric emptying and the production of digestive enzymes so the maximum food absorption and also blood circulation and increase cell metabolism so the baby's weight will be increase.Key words: the effect of the baby therapy. the Weight increase..